Oral hygiene status students of Faculty of Dentistry Universitas Padjadjaran batch 2007 and 2011 - Arista, Stevi Mega; Wardani, Riana; Suwargiani, Anne Agustina (Padjadjaran Journal of Dentistry, 2013)
Introduction: Oral hygiene could be influenced by four factors, there are enviromental, behavior, health service, and hereditery factors. The mayor factors are enviromental and behavior factors. Behavior factors influenced by the level of education a person which  affect to the status of individual oral hygiene. The aim of this research was to describe oral hygiene status on students at Faculty of Dentistry, Universitas Padjadjaran class of 2007 with class of 2011. Methods: This type of research was descriptive research using the survey method were obtained through clinical examination. The sampel were collected by way of proportional sampling and samples were 142 students. Results: Oral hygiene index of students of Faculty of Dentistry, Universitas Padjadjaran class of 2007 to be 0,62. The result of this research indicated that the oral hygiene index of students of Faculty of Dentistry, Universitas Padjadjaran class of  2011 to be 1,19. Conclusion: Oral Hygiene status of students of Faculty of Dentistry Universitas Padjadjaran class of 2007 were in the good category and  the Oral Hygiene Index of students of Faculty of Dentistry Universitas Padjadjaran class of 2011 were in the medium  category.